Investigation on Monitoring System for Pantograph and Catenary Based on Condition-Based Recognition of Pantograph - Ning Zhou; Wenjie Yang; Jiurui Liu; Weihua Zhang; Dong Wang (Shock and Vibration)
In recent years, the length of electrified railway systems has increased along with the number of railway vehicles in China. For the pantograph-catenary system, as one of the key components of the vehicle system, an urgent problem includes diagnosing faults and proposing a safety monitoring system to assure safe operation, improve the level of detection, and decrease the cost of maintenance and repairs. For the monitoring system based on the pantograph, the design process, whole architecture, function module, fault diagnosis method, and monitoring scheme have been investigated. Two specified faults were introduced to describe how to develop such a monitoring scheme based on the pantograph condition-based recognition.